The Effects of "Media Tech Neck": The Impact of Spinal Flexion on Cognitive and Emotional Processing of Videos. - Cores-Sarría, Lucía; Han, Jingjing; Myrick, Jessica G.; Potter, Robert F. (Communication Research, 2023)
Adoption of mobile devices (e.g., smart phones and tablets) has popularized a neck-down posture during media consumption that is different from the traditional upright body posture for video viewing. A neck-down posture exerts substantial pressure upon the spine, and this posture has been previously linked to psychological effects. This study advances the literature by studying the impact of posture effects on processing audiovisual information. In a mixed design experiment (N = 87), the effect of neck posture when viewing 24 video PSAs was tested using physiological and self-report measures. Multilevel modeling analyses of heart rate and corrugator data showed that spinal flexion lowered attentional engagement and caused incongruent emotional responses to the messages compared to a neutral spine posture. However, spinal-flexion participants exhibited greater skin conductance, counter to the predicted emotional disengagement. The impact of neck posture on message processing was largest at the beginning of the experiment and faded over time.